Two children with extra-nodal Mycobacterium avium complex infection. Issue 4 (27th May 2020) - Markland, Ali; Tan, Ben; Adamko, Darryl; Diener, Tania; Levett, Paul N; Wiebe, Sheldon; Wang, Hui; Podberezin, Mark; Saczek, Krysztof; Milbrandt, Kris; Essalah, Abdulhafid; Quan, William; et al.
Abstract: Mycobacterium avium complex (MAC) is usually considered an opportunistic organism, which infects immunocompromised children or those with structural airway abnormalities. We present two cases of MAC infection affecting immune competent children, likely from hot tubs with primary involvement of pulmonary and urinary systems. These cases highlight the importance of asking about hot tub use in immune competent children with suspected or confirmed MAC infections.